THE EFFECTIVENESS OF COCOPEAT AS A PLANTING MEDIA ON THE GROWTH OF SOME OIL PALM VARIETIES (Elaeis guineensis Jacq) - Fenty Maimunah Simbolon; Noverina Chaniago; Abdul Hakim Hutasuhut (PT Inovasi Pratama Internasional, 2022)
The purpose of the study was to determine the growth of several oil palm to the application of cocopeat as a growing medium. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of North Sumatra, Medan, which is located on Jalan . Karya Wisata, Johor Building, Medan Johor District, Madya City, North Sumatra Province with an altitude of ± 25 m above sea level, air humidity (RH) 68% and flat topography. The research was carried out from January-March 2016. This research used a factorial randomized block design (RBD) with two factors, namely: Cocopeat as a planting media mixture consists of 4 levels: C0 = Topsoil (Control) , C1 = Topsoil: cocopeat not soaked (2: 1) , C2 = Topsoil: cocopeat soaked in a bucket (2: 1) , C3 = Topsoil: cocopeat soaked in running water (2: 1) . The use of several varieties of oil palm consists of 3 levels: V1 = Simalungun SP540 DXP , V2 = Yangambi DXP PPKS718 , V3 = Langkat DXP Langkat. The research results showed that the growth of several oil palm varieties had no significant effect on all treatment parameters. The use of cocopeat had a significant effect on the number of leaves, but had no significant effect on plant height, leaf area , leaf chlorophyll, base weight and dry weight. Good growth was seen when cocopeat was soaked in C3 running water. The interaction of cocopeat with several oil palm varieties had a significant effect on the number of leaves of oil palm seedlings, whereas it had no significant effect on the other treatments.